Association Between Food Opportunities During the School Day and Selected Dietary Behaviors of Alternative High School Students, Minneapolis/Saint Paul, Minnesota, 2006 - Chrisa Arcan, PhD, MHS, MBA; Martha Y. Kubik, PhD, RN; Jayne A. Fulkerson, PhD; Cynthia Davey, MS; Mary Story, PhD, RD (Centers for Disease Control and Prevention, 2011)
IntroductionAvailability of competitive foods in schools has been linked to unhealthful dietary behaviors of students. Little is known about the food environment of alternative high schools, schools that enroll students at risk of academic failure. We examined correlations between food opportunities during the school day and selected dietary behaviors of students attending alternative high schools.MethodsBaseline data were collected in fall 2006 as part of the Team COOL (Controlling Overweight and Obesity for Life) pilot study, a group randomized obesity prevention trial. Students (n = 145) attending 6 alternative high schools in Minneapolis/Saint Paul, Minnesota, completed a survey on food opportunities during the school day and selected dietary behaviors. We used mixed-model multivariate cross-sectional analysis and adjusted for demographic characteristics to examine associations of interest.ResultsFood opportunities during the school day were positively associated with overall consumption of sugar-sweetened beverages, high-fat foods, and fast-food restaurant use.ConclusionsHaving many food opportunities during the school day at alternative high schools was linked to the consumption of foods and beverages high in sugar and fat and low in nutrients. School-based interventions should focus on changing the food environment in alternative high schools to decrease less healthful eating opportunities and to increase the availability of healthful foods and beverages.